The effect of lead exposure of mice during pregnancy on the morphology of epididymal and testicular spermatozoa of their offspring - Al-Ani, Imad Matloub Dally; Al-Khfaji , Imaa'am; Fakhrildin, Mihamed-Baqer; Mangalo, Han'aa; Al-Obaidi, Salim Rasheed (Kulliyyah of Medicine, International Islamic University Malaysia, 2009)

(untitled)
The aims of this study were to assess the differences in the percentages of abnormal morphology between the epididymal and testicular spermatozoa of mature male offspring mice whose mothers were injected with various doses of lead acetate during gestation. Seventy two healthy female mice were divided into three major groups according to the number of injections involving 1, 2 or 3 injections at 8th day; 8th and 13th days; and 8th, 13th and 18th days of gestation period, respectively. Each major group was subdivided into four minor groups according to of the dosage of lead administration of (0, 25, 50 and 100) mg/Kg. The percentages of abnormal morphology of epididymal and testicular spermatozoa were studied and the data were statistically analyzed. The results of the present study proved that an increased number of injections and/or dose of lead acetate injected to the mothers during gestation cause an elevation in the percentage of abnormal morphology of both epididymal and testicular spermatozoa of the male mice offspring. In conclusion this study demonstrated that lead acetate when exposed prenatally have toxic effects on the sperm abnormal morphology in the offspring male mice most likely by interfering with the phase(s) of spermatogenesis and/or spermiogenesis.